Photocross-Linkable and Shape-Memory Biomaterial Hydrogel Based on Methacrylated Cellulose Nanofibres - Brusentsev Yury; Yang Peiru; King Alistair W.T.; Cheng Fang; Cortes Ruiz Maria F.; Eriksson John E.; Kilpeläinen Ilkka; Willför Stefan; Xu Chunlin; Wågberg Lars; Wang Xiaoju (AMER CHEMICAL SOC, 2025)
In the context of three-dimensional (3D) cell cultureand tissueengineering, 3D printing is a powerful tool for customizing in vitro3D cell culture models that are critical for understanding the cell-matrixand cell-cell interactions. Cellulose nanofibril (CNF) hydrogelsare emerging in constructing scaffolds able to imitate tissue in amicroenvironment. A direct modification of the methacryloyl (MA) grouponto CNF is an appealing approach to synthesize photocross-linkablebuilding blocks in formulating CNF-based bioinks for light-assisted3D printing; however, it faces the challenge of the low efficiencyof heterogenous surface modification. Here, a multistep approach yieldsCNF methacrylate (CNF-MA) with a decent degree of substitution whilemaintaining a highly dispersible CNF hydrogel, and CNF-MA is furtherformulated and copolymerized with monomeric acrylamide (AA) to forma super transparent hydrogel with tuneable mechanical strength (compressionmodulus, approximately 5-15 kPa). The resulting photocurablehydrogel shows good printability in direct ink writing and good cytocompatibilitywith HeLa and human dermal fibroblast cell lines. Moreover, the hydrogelreswells in water and expands to all directions to restore its originaldimension after being air-dried, with further enhanced mechanicalproperties, for example, Young's modulus of a 1.1% CNF-MA/1%PAA hydrogel after reswelling in water increases to 10.3 kPa from5.5 kPa.